ANALISIS PENGARUH PRINSIP-PRINSIP GOOD CORPORATE GOVERNANCE PADA UMKM DI KOTA BANJARMASIN - Nurlida, Ied Nabilah; Ghalib, Saladin (Universitas lambung Mangkurat, 2020)
Ied Nabilah Nurlida, D1A215045, 2019 ?The analysis on the application of the principles of Good Corporate Governance at SMEs in Banjarmasin?, Essay. Programme of Study in Business Administration. Advisor : Saladin Ghalib. MSME (Micro, Small and Medium Enterprises) has a crucial role in improving an economy because its number of business units keeps growing rapidly, contributing 60% of GDP and being able to absorb large numbers of workers, namely 97% of the total workforces in Indonesia. However, MSME's also have characteristics which contain potential weaknesses which could create problems. Therefore, MSME's need to implement a good governance for their businesses, one of which is by applying the principles of Good Corporate Governance. This study aims to analyze the application of the principles of Good Corporate Governance at MSME's in Banjarmasin. This study is a qualitative research with a phenomenological approach, using descriptive analysis method and descriptive research type. Data collection techniques uses observation, documentation, and interviews. Data analysis techniques uses the qualitative interactive model of Miles and Huberman. The results of this study indicates that the studied MSME's have applied the principles of GCG in their business, although the size of the application itself varies for each one of them. (1) The principle of transparency has been well applied through the delivery of information orally and in writing in the form of simple notes or MSME's which tend to be willing to make good financial reports due to capital requirements from the bank or the government. (2) The principle of accountability has been well implemented because there are details of the duties and responsibilities of each employee, the manager whose duty is to ensure that his employees produce good performance and are consistent in maintaining food quality. (3) The principle of responsibility has been applied quite well especially for MSME's whose capital is assisted by banks or the government where they are required to have a business license, in addition MSME's have responsibilities towards their workers and consumers. (4) The principle of independence has been implemented very well because generally MSME's tend to run family businesses. (5) The principle of fairness has been implemented excelently through an equal payroll system, providing opportunities to express opinions to stakeholders and fairness to consumers through the quality of food and services provided.